Corrigendum to “Linking microbial functional partitioning with methane productivity and stability in microbial electrolysis cell–anaerobic digestion hybrid systems” [Bioresour. Technol. 453 (2026) 134629] - Xue-Ting Wang; Yanxue Li; Yuxin Pan; Xue Xing; Bo Wang; Defeng Xing; Jun Nan; Jonathan Tian En Lee; Eakalak Khan; Daniel C.W. Tsang; Nan-Qi Ren; Yong Sik Ok (Bioresource Technology, 2026)

Linking microbial functional partitioning with methane productivity and stability in microbial electrolysis cell–anaerobic digestion hybrid systems - Xue-Ting Wang; Yanxue Li; Yuxin Pan; Xue Xing; Bo Wang; Defeng Xing; Jun Nan; Jonathan Tian En Lee; Eakalak Khan; Daniel C.W. Tsang; Nan-Qi Ren; Yong Sik Ok (Bioresource Technology, 2026)

Bioaugmentation of strain Bacillus sp. hex-HIT36 towards industrial wastewater 1-Hexadecene removal in biological aerated filter reactors - Lei Yang; Yijie Liu; Yuxin Pan; Xue-Ting Wang; Wei Wang; Xijun Xu; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Chemical Engineering Journal, 2026)

Development of real‐time recombinase polymerase amplification ( RPA ) and RPA combined with lateral flow dipstick ( LFD ) assays for the rapid and sensitive detection of cyprinid herpesvirus 3 - Yingying Li; Ruifan Li; Xubing Mo; Yingying Wang; Jiyuan Yin; Sven M. Bergmann; Yan Ren; Houjun Pan; Cunbin Shi; Defeng Zhang; Qing Wang (Journal of Fish Diseases, 2024)
In this issue, we established rapid, cost‐effective, and simple detection methods including recombines polymerase amplification with lateral flow dipstick (RPA‐LFD) and real‐time RPA for cyprinid herpesvirus 3(CyHV‐3), and evaluated their sensitivity, specificity, and applicability, the real‐time RPA method could achieve sensitive diagnosis of CyHV‐3 within 1.3 copies per reaction, respectively. The real‐time RPA method is 10‐fold more sensitive than RPA‐LFD method. The exact number of CyHV‐3 can be calculated in each sample by real‐time RPA. The sera from koi also can be tested in these methods. In addition, no cross‐reaction was observed with other related pathogens, including carp oedema virus (CEV), spring viraemia of carp virus (SVCV), cyprinid herpesvirus 1(CyHV‐1), cyprinid herpesvirus 2(CyHV‐2), type I grass carp reovirus (GCRV‐I), type II GCRV (GCRV‐II), type III GCRV (GCRV‐III), and Aeromonas hydrophila.

Water-saving irrigation and delayed sowing increased the emission intensity of CH4 and N2O in the rice-wheat rotated field under nighttime warming - Yunsheng Lou; Jun Li; Junhong Guo; Defeng Pan; Zhen Zhang; Li Ma; Rui Li; Lixuan Ren (Agriculture, Ecosystems & Environment, 2024)

Investigation into the treatment and resource recovery of rifamycin mycelial dreg with thermal alkaline pretreatment-anaerobic digestion - Quan Zhang; Xuejiao Gong; Yu Zhang; Xueting Wang; Xiaowen Pan; Yanfeng Zhou; Xijun Xu; Qi Zhang; Xiao-Ming Ji; Weijun Wang; Defeng Xing; Nanqi Ren; et al. (Journal of Cleaner Production, 2023)

Formation of PCDD/Fs, PCBs and HCl during catalytic combustion of chlorobenzene over supported transition metal (Cr, V and Cu) oxide catalysts - Defeng Xing; Sheng Wang; Yun Fan; Haijun Zhang; Ting Wang; Mingzhe Wang; Shudong Wang; Jiancheng Wang; Dahai Pan; Xueding Song (Journal of Environmental Chemical Engineering, 2023)

Do ectoparasites on fish gills “talk” with gut microbiota far away? - Lin Wang; Defeng Zhang; Jun Xie; Ouqin Chang; Qing Wang; Cunbin Shi; Fei Zhao; Hua Gong; Yan Ren; Najiah Musa; Kok Leong Lee; Houjun Pan (Aquaculture, 2023)

Spatial-temporal dynamics of soil chloride distribution in a coastal saline plain: implication for ocean and climate influences - Shaofeng Yan; Lu Zhai; Qiuliang Deng; Defeng Pan; Shikai Gao; Chaowang Zou (Journal of Soils and Sediments, 2018)